Chemical stimulation techniques for geothermal wells: experiments on the three-well EGS system at Soultz-sous-Forêts, France - Portier, Sandrine; Vuataz, François; Nami, Patrick; Sanjuan, Bernard; Gérard, André (My University, 2009)
Rock matrix stimulation is a method of enhancing well production or injection within a broad range of challenging environments, varying from naturally fractured limestones to sandstones with complex mineralogy. A common and often successful stimulation option, matrix acidizing, utilizes acids that react and remove mineral phases restricting fluid flow. Reviewed is the technology of chemical treatments available for oil, gas and geothermal wells and the key elements and results of the chemical reservoir stimulation program at the Soultz-sous-Forêts, France, Enhanced Geothermal System Project.
Keywords: Enhanced Geothermal Systems; Scaling; Chemical stimulation; Acid injection; Chelating agent; Well cleaning; Fractured granite; Soultz-sous-Forêts; France